The development of HPLC-MC as a method of purity assessment and confirmation the molecular mass of new bioactive compounds - B. A. Varynskyi (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The flow-injection analysis with mass-spectrometric detection (FIA-MS) was the first widespread system of the fast determination of the molecular mass. Then open access systems based on high-performance liquid chromatography with mass-spectrometric detection (HPLC -MS) became popular.